A global overview of biodiversity offsetting governance. (15th August 2022) - Droste, Nils; Alkan Olsson, Johanna; Hanson, Helena; Knaggård, Åsa; Lima, Guilherme; Lundmark, Linda; Thoni, Terese; Zelli, Fariborz
Abstract: We analyze the development of biodiversity offsetting governance through a research-weaving approach. Here, we combine information from a systematized review of the literature and a qualitative analysis of the institutional developments in different world regions. Through this triangulation, we synthesize and map the different developmental streams of biodiversity offsetting governance around the globe over the last four decades. We find that there is a global mainstreaming of core principles such as avoidance, no-net-loss, and a mitigation hierarchy, as well as pooling and trading of offsets for unavoidable residual damages. Furthermore, we can observe an ongoing diversification of institutional designs and actors involved. Together this constitutes an emerging regime complex of biodiversity offsetting governance that comes with both a set of shared norms and a growing institutional complexity. While this may imply institutional innovation through diversification and policy experimentation, it also raises questions regarding the effectiveness of offsetting practices. Highlights: Mapping biodiversity offsetting governance around the globe. Showing developments based on a quantitative topic model and a qualitative review. Finding a global mainstreaming of core principles such as no-net loss and mitigation hierarchies. Observing an institutional diversification through adaptation to local regulatory contexts. We conclude that there is an emerging regime complex of biodiversity offsetting governance.